How to reconstruct Ukraine - Anders Åslund (EconPol Forum, 2023)
The Ukrainian state budget needs about 3.5 billion a month to keep afloat in 2023. The main donors must be the United States and the European Union. Three key tasks need to be combined: reconstruction, EU accession, and completion of systemic reforms. The collective West needs to set up a joint steering group with the Ukrainian government for the management of the reconstruction, EU accession, and completion of reform with good governance and eminent transparency. The costs of the damages that Russia has incurred on Ukraine are enormous. Russia must be forced to pay war reparations. Fortunately, more than 300 billion of currency reserves of the Central Bank of Russia has been frozen in Western central banks. They should be confiscated and used for Ukrainian reconstruction. Reconstruction should be based on the principles of insurance, covering the costs of each person or entity that has suffered losses from Russian aggression. At the same time, the Ukrainian government and the EU need to reorient strategic infrastructure from Russia to the EU.
Keywords: 330